Validitas Job Sheet Mikrokontroler Menggunakan Bahasa Pemrograman C - Suyono Suyono; Mukhlidi Muskhir (Jurnal Pendidikan Teknik Elektro, 2021)
This research aimed to analyzed The validity level of learning media in job sheet microcontroller using programming languages C for practical Works microcontroller subject industrial electrical engineering (D4), electrical engineering department, faculty of engineering, UNP. The Research is done by using tests and get the data in the electrical engineering department, faculty of engineering, UNP. The research method that using: (1) validation job sheet by using 4 validators, validation sheet, (2) validity test, (3) reliability test. The test result of learning media is fulfilling the condition of validity to visual element component value 0,83 with very valid category, for languages component value 0,88 with a very valid category. Thus, learning media in job sheet microcontroller categorized very valid as learning media and can be used as practical work guide for independent study after valued 4 validators with average value 0,81, reliability level value 0,642 in category moderate (medium), with research data percentage 35-63%.